PENGELOLAAN KEKAYAAN HAYATI DI KAWASAN “THE AREA” MENURUT UNCLOS 1982 [STUDI TENTANG NODUL POLIMETALIK (POLYMETALLIC NODULES)] - H A S, Yasin Nur A; Soelistyo, Liem Tony Dwi; Agustin, Ika Shinta Utami Nur (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
Beautiful and challenging seabed charms and rapid developments in technology for deep sea exploration and exploitation have occurred during the negotiations of the United Nations Convention on the Law of the Sea 1982. The development of this technology can give us broader knowledge about wealth in the deep sea floor. Significantly known deposits on the seabed outside national jurisdiction and named the Area or